Police Departments' Use of Lethality Assessments: An Experimental Evaluation - Messing, Jill ([Verlag nicht ermittelbar], 2015)
Police Departments' Use of Lethality Assessments: An Experimental Evaluation examined the effectiveness of the Lethality Assessment Protocol (LAP), a tool used to gauge the severity of danger to victims of intimate partner violence (IPV) and determine whether to immediately connect victims with additional resources and safety options. Specifically, the evaluation focused on the effectiveness of the LAP at decreasing the rates of repeat, lethal and near lethal violence and increasing the rates of emergency safety planning and help seeking among women who experienced IPV and called the police. Additionally, the predictive and concurrent validity of the screening portion of the LAP was evaluated, as were the implementation of the LAP by officers and IPV victims' satisfaction with the police responses they experienced. The study consisted of two groups: (1) a comparison group, which included women who were victims of IPV and were referred to the study by a police officer; and (2) an intervention group which consisted of victims of IPV who were administered the LAP by police. Both groups were contacted for baseline and follow-up phone interview surveys that recorded the victims' self-reported demographic information (age, race, income, education marital status), information about the status of their relationships with their partners, as well as the type of abuse they had endured and how this affected their behavior.